Apoptotic pathways are selectively activated by granzyme A and/or granzyme B in CTL-mediated target cell lysis - Pardo, Julián; Bosque, Alberto; Brehm, Reina; Wallich, Reinhard; Naval, Javier; Müllbacher, Arno; Anel, Alberto; Simon, Markus M. (The journal of cell biology, 2004)
Purified cytolytic T lymphocyte (CTL) proteases granzyme (gzm)A and gzmB with sublytic dose of perforin (perf) initiate distinct proapoptotic pathways. Their physiological relevance in CTL-mediated target cell apoptosis is elusive. Using ex vivo virus-immune CD8(+) T cells from mice deficient in perf, gzmA and/or gzmB, and the Fas-resistant EL4.F15 tumor target cell, we show that (a) CTL from gzmA(-/-) or gzmB(-/-) mice similarly induced early proapoptotic features, such as phosphatidyl serine (PS) exposure on plasma membrane, Delta Psi(m) loss, and reactive oxygen radical generation, though with distinct kinetics; (b) CTL from gzmA(-/-) but not from gzmB(-/-) mice activate caspase 3 and 9; (c) PS exposure induced by CTL from gzmA(-/-) or gzmB(-/-) mice is prevented, respectively, by caspase inhibitors or by reactive oxygen scavengers without interfering with target cell death; and (d) all gzm-induced apoptotic features analyzed depend critically on perf. Thus, perf is the principal regulator in CTL-mediated and gzm-facilitated intracellular processes. The ability of gzmA and gzmB to induce multiple independent cell death pathways may be the hosts response to circumvent evasion strategies of pathogens and tumors.